2017
DOI: 10.1371/journal.pgen.1006728
|View full text |Cite|
|
Sign up to set email alerts
|

Single-trait and multi-trait genome-wide association analyses identify novel loci for blood pressure in African-ancestry populations

Abstract: Hypertension is a leading cause of global disease, mortality, and disability. While individuals of African descent suffer a disproportionate burden of hypertension and its complications, they have been underrepresented in genetic studies. To identify novel susceptibility loci for blood pressure and hypertension in people of African ancestry, we performed both single and multiple-trait genome-wide association analyses. We analyzed 21 genome-wide association studies comprised of 31,968 individuals of African anc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
95
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 95 publications
(106 citation statements)
references
References 81 publications
10
95
1
Order By: Relevance
“…There are fewer loci reaching GWAS significance in African populations than in Europeans or Asians. The largest GWAS performed in an African-origin population analyzed 21 GWAS comprising 31,968 individuals of African ancestry and validated their results with an additional 54,395 individuals from multiethnic studies [15]. The authors found 9 loci with 11 independent variants for either SBP, DBP, hypertension, or combined traits.…”
Section: Gwas-significant Locimentioning
confidence: 96%
“…There are fewer loci reaching GWAS significance in African populations than in Europeans or Asians. The largest GWAS performed in an African-origin population analyzed 21 GWAS comprising 31,968 individuals of African ancestry and validated their results with an additional 54,395 individuals from multiethnic studies [15]. The authors found 9 loci with 11 independent variants for either SBP, DBP, hypertension, or combined traits.…”
Section: Gwas-significant Locimentioning
confidence: 96%
“…This research identified three novel genomic regions associated with blood pressure and utilized transomic techniques to unravel the associated pathways, which have not been previously reported in studies of other race/ethnicity. 62 Likewise, stroke research utilizing Africans and African ancestry populations can produce significant dividends because of the association between high blood pressure and stroke in African ancestry populations. 62 …”
Section: 0 Discussionmentioning
confidence: 99%
“…62 Likewise, stroke research utilizing Africans and African ancestry populations can produce significant dividends because of the association between high blood pressure and stroke in African ancestry populations. 62 …”
Section: 0 Discussionmentioning
confidence: 99%
“…Together, these efforts have already yielded the successful discovery of over thousands of disease associated loci (Ehret et al, 2016; Ehret et al, 2011; Evangelou, 2018; Hoffmann et al, 2017; Lane et al, 2016; Liang et al, 2017; Liu et al, 2016; Marouli et al, 2017; Turcot et al, 2018). The commonly-used approach for analyzing a continuous trait still relies on a simple regression model.…”
Section: Introductionmentioning
confidence: 99%
“…Genome-wide association studies (GWAS), whole-exome sequencing studies and whole-genome sequencing studies have produced many large data sets of genetic variation in hundreds of thousands to millions of human subjects (Boyle, Li, & Pritchard, 2017), which has motivated the development of new statistical methods to analyze these data sets for addressing important biological questions. Together, these efforts have already yielded the successful discovery of over thousands of disease-associated loci (Ehret et al, 2011;Ehret et al, 2016;Evangelou, Warren & Mosen-Ansorena, 2017;Hoffmann et al, 2017;Lane et al, 2016;Liang et al, 2017;Liu et al, 2016;Marouli et al, 2017;Turcot et al, 2018). The commonly used approach for analyzing a continuous trait still relies on a simple regression model.…”
Section: Introductionmentioning
confidence: 99%